Inventarisasi Cendawan Terbawa Benih Padi, Kedelai, dan Cabai - Evan Purnama Ramdan; Ummu Kalsum (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2017)
The use of good quality seeds is one of important factors in success of agricultural production because it could increase production and reduced existence of disease problems in the field. The entry of seeds to a country pass through import activities has potential to become enter new pathogen medium, so it needed to detect and indentify fungi in the seeds. The aims  of this study were to inventory seed-borne fungi and its effect on seed germination potential. This research has been conducted at Education Laboratory of Protection Department, Bogor Agricultural University during five months (March until July 2013). The experiment was arranged in completely randomized one factor. The factor was pathogen infection. Each seed detected fungi existence with blotter test method and seed germination test. The result showed seed-borne fungi were Colletrotrichum sp. and Rhizopus sp in chilli seed, Curvularia sp., Aspergillus sp., and Penicillium soybean seeds, Aspergillus sp. in rice seeds. The highest seed germination percentage in soybean seeds almost 100% in both of paper methods, whereas the lowest was rice seeds. All of seed germination medium, chilli showed lowest germination percentage, i.e. 68 - 76.27% with highest fungi association of Aspergillus sp. dan Fusarium sp. up to 52%. Aspergillus sp dan Fusarium sp may caused decreasing seed viability and vigor of chilli.